No Skin Paddle, No Problem: Burying Deep Inferior Epigastric Artery Flaps in the Immediate Setting is Safe in Select Patient Populations - Lignieres, Austin; Andejani, Doaa F.; Chu, Carrie K.; Largo, Rene D.; Mericli, Alexander F. (Journal of Reconstructive Microsurgery, 2024)
Background In appropriately selected patients, it may be possible to fully bury breast free flaps deep to the mastectomy skin flaps. Because this practice forgoes the incorporation of a monitoring skin paddle for the flap, and thus limits the ability for physical exam, it may be associated with an increased risk of flap loss or other perfusion-related complications, such as fat necrosis. We hypothesized that fully de-epithelialized breast free flaps were not associated with an increased complication rate and reduced the need for future revision surgery.Methods A single-institution retrospective review of 206 deep inferior epigastric artery (DIEP) flaps in 142 patients was performed between June 2016 and September 2021. Flaps were grouped into buried or nonburied categories based on the absence or presence of a monitoring paddle. Patient-reported outcomes were assessed postoperatively using the BREAST-Q breast reconstruction module. Electronic medical record data included demographics, comorbidities, flap characteristics, complications, and revision surgery.Results The buried flap patients (N = 46) had a lower median body mass index (26.9 vs 30.3, p = 0.04) and a lower rate of hypertension (19.5 vs. 37.5%, p = 0.04) compared with nonburied flap patients (N = 160). Burying flaps was more likely to be adopted in skin-sparing mastectomy or nipple-sparing mastectomy (p = 0.001) and in an immediate or a delayed–immediate fashion (p = 0.009). There was one flap loss in the nonburied group; complication rates were similar. There was a significantly greater revision rate in the nonburied flap patients (92 vs. 70%; p = 0.002). Buried flap patients exhibited a greater satisfaction with breasts (84.5 ± 13.4 vs. 73.9 ± 21.4; p = 0.04) and sexual satisfaction (73.1 ± 22.4 vs. 53.7 ± 29.7; p = 0.01) compared with nonburied flap patients.Conclusion Burying breast free flaps in appropriately selected patients does not appear to have a higher complication rate when compared with flaps with an externalized monitoring paddle. Furthermore, this modification may be associated with a better immediate aesthetic outcome and improved patient satisfaction, as evidenced by a lower rate of revision surgery and superior BREAST-Q scores among buried DIEP flaps.
Keywords: breast reconstruction; surgical flaps; breast cancer